2019
DOI: 10.5694/mja2.50142
|View full text |Cite
|
Sign up to set email alerts
|

An updated review of lipid‐modifying therapy

Abstract: Summary Statin drugs reduce low‐density lipoprotein (LDL)‐cholesterol (LDL‐C) and cardiovascular risk. Ezetimibe may be used to supplement statin therapy, or used alone in cases of statin intolerance. Statin‐associated side effects do occur, especially muscle symptoms and new onset diabetes, but they do not detract from the benefits of statin therapy. Inhibitors of proprotein convertase subtilisin/kexin type 9 (PCSK9) reduce LDL‐C and cardiovascular risk. Evolocumab is subsidised in Australia for patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 66 publications
(79 reference statements)
0
8
0
Order By: Relevance
“…[6][7][8][9] They also suggest that modifications in dietary habits and lifestyle have crucial roles in reducing the risk of CVDs through a variety of mechanisms and are much more important than genetic factors. [10][11][12] American Heart Association guidelines for management of blood cholesterol levels are consistent with these findings. [13] Epidemiological studies and meta-analysis have consistently found a negative association between the risk of CVDs and whole-grain consumption.…”
Section: Introductionmentioning
confidence: 55%
See 1 more Smart Citation
“…[6][7][8][9] They also suggest that modifications in dietary habits and lifestyle have crucial roles in reducing the risk of CVDs through a variety of mechanisms and are much more important than genetic factors. [10][11][12] American Heart Association guidelines for management of blood cholesterol levels are consistent with these findings. [13] Epidemiological studies and meta-analysis have consistently found a negative association between the risk of CVDs and whole-grain consumption.…”
Section: Introductionmentioning
confidence: 55%
“…[ 6–9 ] They also suggest that modifications in dietary habits and lifestyle have crucial roles in reducing the risk of CVDs through a variety of mechanisms and are much more important than genetic factors. [ 10–12 ] American Heart Association guidelines for management of blood cholesterol levels are consistent with these findings. [ 13 ]…”
Section: Introductionmentioning
confidence: 61%
“…15 Duration of treatment brings cumulative benefit, especially when started early in life. 5,15,42,43 Future medications that target…”
Section: International Approaches To Risk Assessmentmentioning
confidence: 99%
“…Statin adherence and persistence is often poor, lacking patient benefit if not taken. 42 Initial patientdoctor discussion should seek consensus on treatment need, stratification of risk involved as well as planned approach involving diet, regular exercise, lifestyle changes and potential pharmacotherapy. Supportive counselling from pharmacists as well as new electronic reminder devices, including texting, can also help adherence.…”
Section: Adherencementioning
confidence: 99%
“…Cholesterol is deeply involved in numerous molecular mechanisms leading to vascular damage; therefore, its concentration is widely used as a diagnostic clinical parameter to assess atherosclerotic disease and risk [2]. Most importantly, backgrounds of hypercholesterolemia can be mainly separated between those deriving from lifestyle, with a significant role of the quality and quantity of nutritional intake, and, much less frequently, those deriving from genetic factors [3].…”
Section: Introductionmentioning
confidence: 99%